(untitled) (Estudios humanísticos. Geografía, historia y arte, 1995)
This study investigates religiousness and social customs surrounding death in the region of "El Bierzo" during the eighteenth century, using wills as a documentary source. There are two main conclusion in the study. Firstly, no qualitative changes can be appreciated in religiousness nor in attitudes towards death throughout the eighteenth century. Secondly, in "El Bierzo" ás in the rest of Spain, Baroque piety does not cease to exist, nor is there a move towards dechistianization as shown in studies carried out in France. Rather, this study shows a process of secularization and of a move away from such great respect for all matters concerning the church.